2022
DOI: 10.1111/odi.14428
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis severity relationship with metabolic syndrome: A systematic review with meta‐analysis

Abstract: The objective of this study was to investigate the association between periodontitis severity and metabolic syndrome (MetS) through systematic review, registered in PROSPERO: CRD42021232120. Selected articles were independently chosen by three reviewers from six databases, including using article reference lists, up until March 2022. Eligible studies were observational, without language limitation, and in subjects aged at least 18 years. The methodological quality of selected studies was assessed using the New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Patients with MS present approximately two times higher risk to develop periodontitis than the rest of the population 32 . On the other hand, periodontitis increases the risk of worsening metabolic and systemic inflammatory parameters in these patients 4,33 . Thus, strategies with effects on these conditions with bidirectional relations are crucially needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with MS present approximately two times higher risk to develop periodontitis than the rest of the population 32 . On the other hand, periodontitis increases the risk of worsening metabolic and systemic inflammatory parameters in these patients 4,33 . Thus, strategies with effects on these conditions with bidirectional relations are crucially needed.…”
Section: Discussionmentioning
confidence: 99%
“…32 On the other hand, periodontitis increases the risk of worsening metabolic and systemic inflammatory parameters in these patients. 4,33 Thus, strategies with effects on these conditions with bidirectional relations are crucially needed. These prevention or treatment alternatives could even exert a major influence in public health programs worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory process in periodontal tissues may release several cytokines into the systemic circulation along with bacterial toxins potentially aggravating the IR. There is also clear evidence for a significant association between MetS and periodontitis as evidenced by a very recent systematic review examining the interlink[ 15 ]. This meta-analysis, including 24567 participants from 14 studies, showed that the adjusted odds ratio (OR) for MetS among patients with moderate periodontitis was 1.26 and those with severe periodontitis was 1.50.…”
Section: Pathobiological Interlink Between Periodontitis and Dmmentioning
confidence: 99%
“…[2][3][4] According to research, there are several additional chronic diseases like cancer, diabetes, cardiovascular disease (CVD), and neurological disorders that are associated with periodontitis. [5][6][7][8][9][10][11][12][13] This work was supported by the Fuzhou Key Specialty Project (Grant number 20191005), and the Fuzhou "14th Five-Year Plan" Clinical Specialty Training and Cultivation Construction Project, (Grant number 20220103).…”
Section: Introductionmentioning
confidence: 99%
“…[2–4] According to research, there are several additional chronic diseases like cancer, diabetes, cardiovascular disease (CVD), and neurological disorders that are associated with periodontitis. [5–13] Therefore, determining periodontitis risk is crucial for the avoidance and management of related chronic diseases.…”
Section: Introductionmentioning
confidence: 99%